Exploiting Blockchain Technology for Enhancing Digital Twins’ Security and Transparency - Alessio Ferone; Stefano Verrilli (Future Internet)
Blockchain technology has been applied in a wide range of domains and has seen major developments in the last years, notably when integrated with other emerging technologies. In this paper, we focus on the integration of blockchain and digital twins with the aim of enhancing the capabilities of both technologies. In particular, we demonstrate how blockchain can improve critical aspects of the security and transparency of digital twins by analyzing a real-world scenario and evaluating produced experimental data. This research identifies and addresses critical vulnerabilities in digital twins, particularly data integrity and transparency, through blockchain-based validation mechanisms and smart-contract integration. Various blockchain-related and digital twin-related technologies are employed to enable the repeatability of the suggested approach. Additionally, an in-depth analysis of such integration is provided to facilitate a symbiotic relationship between these technologies by addressing key challenges, such as scalability, interoperability, and performance, along with viable solutions that could advance their co-evolution in both academic research and industrial applications.